Abnormal proprioceptive-motor integration contributes to hypometric postural responses of subjects with parkinson’s disease - Jacobs, J.V.; Horak, F.B. (Neuroscience, 2006)
Subjects with Parkinson’s disease exhibit abnormally short compensatory steps in response to external postural perturbations. We examined whether: (1) Parkinson’s disease subjects exhibit short compensatory steps due to abnormal central proprioceptive-motor integration, (2) this proprioceptive-motor deficit can be overcome by visual–motor neural circuits using visual targets, (3) the proprioceptive-motor deficit relates to the severity of Parkinson’s disease, and (4) the dysfunction of central dopaminergic circuits contributes to the Parkinson’s disease subjects’ proprioceptive-motor deficit. Ten Parkinson’s disease subjects and 10 matched control subjects performed compensatory steps in response to backward surface translations in five conditions: with eyes closed, with eyes open, to a remembered visual target, to a target without seeing their legs, and to a target while seeing their legs. Parkinson’s disease subjects were separated into a moderate group and a severe group based on scores from the Unified Parkinson’s Disease Rating Scale and were tested off and on their dopamine medication. Parkinson’s disease subjects exhibited shorter compensatory steps than did the control subjects, but all subjects increased their step length when stepping to targets. Compared with the other subject groups, the severe Parkinson’s disease subjects made larger accuracy errors when stepping to targets, and the severe Parkinson’s disease subjects’ step accuracy worsened the most when they were unable to see their legs. Thus, Parkinson’s disease subjects exhibited short compensatory steps due to abnormal proprioceptive-motor integration and used visual input to take longer compensatory steps when a target was provided. In severe Parkinson’s disease subjects, however, visual input does not fully compensate because, even with a target and unobstructed vision, they still exhibited poor step accuracy. Medication did not consistently improve the length and accuracy of the Parkinson’s disease subjects’ compensatory steps, suggesting that degeneration of dopamine circuits within the basal ganglia is not responsible for the proprioceptive-motor deficit that degrades compensatory steps in Parkinson’s disease subjects.